Glioblastoma. Past, present and future - Adriel Herrero Díaz; Luis Manuel Abreu Pereira; Ilian Esteban Tarife Romero; Diana Rosa González Tamayo (Medisur)
Glioblastoma is the most advanced, common and malignant stage of primary brain tumors in adults. It represents about 57% of all glial tumors. In adults it is more common in the cerebral hemispheres, while in children it is more common in the posterior fossa. Its infiltrative growth is extremely rapid. The present literature review aims to describe the clinical characteristics and treatment of glioblastoma as an aggressive brain tumor. A bibliographic search was carried out, resulting in 29 bibliographic sources, available in Scielo, PubMed, Dialnet and Elsevier, in which the information reviewed, was supported. Grade IV glioblastoma or astrocytoma is an aggressive, poorly differentiated tumor with a high degree of malignancy, invariably associated with a poor prognosis. Glioblastoma is positioned as the most aggressive form of brain cancer. Its treatment is based on tumor cytoreduction, combined with chemo and radiotherapy. The current numbers show unfavorable prognoses associated with this neoplasia. The improvement and creation of new anticancer therapies are the future hopes in the fight against this pathology.